MODEL OPTIMASI KAPASITAS INDUSTRI PADA KLASTER INDUSTRI HILIR KELAPA SAWIT DI KAWASAN INDUSTRI SEI MANGKEI - Indrani Dharmayanti, Hartrisari Hardjomidjojo, Anas Miftah Fauzi, Dedi Mulyadi (Jurnal Teknologi Industri Pertanian, 2017)
Palm oil industrial cluster development in Sei Mangkei is a step to realize the downstream programme, increase the added value and competitiveness through integrated management. To optimize the development, it is necessary to make the planning starting from the selection of potential industries, as well as calculate how optimal capacity, with the availability of raw materials as constraints.  The selection of products is done with the exponential comparison method with the result that industrial cooking oil, margarine, basic oleo chemicals, surfactants, biodiesel, industrial soap, liquid soap, shampoo and detergents, as well as biogas and animal feed were potential for development in the industrial park. The goal programming analysis was performed to determine the optimal industrial  capacity that provide maximum benefit and labour, and minimal waste produces. Based on the optimization analysis, the profits target was achieved and the largest profits derived from basic oleochemical industry, margarine, cooking oil, and soap bars. While labour targets were not achieved, because labour absorption  less than 80% of the target. The target of waste was achieved,  and the largest proportion of liquid waste was produced by cooking oil and basic oleochemicals industry. This model is expected to illustrate the capacity calculation model of industry in other cluster development.Keywords: goal programming, industrial park, optimization, palm oil industrial cluster,